Corporate Transparency in Iran and Its Influential Factors - Hamid Khaleghi Moghaddam; Alireza Khalegh (مطالعات تجربی حسابداری مالی, 2008)
In this research study, we have used the Transparency and Disclosure scores set by Standard & Poors for evaluation and trend analysis of transparency of the companies listed in Tehran Stock Exchange. We have also examined the correlation of transparency scores with some factors such as: size of the companies, leverage ratios, profitability, ownership structure, and number of independent board members. This research study indicates that the Corporate Transparency score was 28 percent in the year 2001 and increased to 32 percent in 2007. Comparison of this result with the studies performed abroad by Standard & Poors reveals the weak position of Iran in Corporate Transparency among other Asian countries, Europeans and also Latin Americans. In addition, we found a positive correlation between the Corporate Transparency and size of the companies but there was no correlation with the other factors mentioned above. Based on the results of this study, we are of the opinion that at present, the companies have no motivation for increasing the Corporate Transparency.